KONCEPCJE KULTURY A NAUCZANIE I UCZENIE SIĘ JĘZYKÓW OBCYCH – ZARYS TEORETYCZNY - Mihułka, Krystyna (Neofilolog, 2018)
Culture has been the subject of researchers’ consideration for centuries, which is confirmed by hundreds of published definitions of the word culture. Even a perfunctory analysis of those definitions indicates that it is difficult to talk about culture using it as a consistent concept. The aim of this article is therefore to highlight the richness of meaning of the word culture by presenting and discussing the characteristics of culture which appear most frequently in definitions developed by social psychologists, cultural anthropologists, social pedagogues, foreign language acquisition researchers, and students of German philology. The final part of this article presents those features of culture which allow to place this concept correctly in the process of foreign language teaching and learning.